Protein–Protein Interaction between Surfactant Protein D and DC-SIGN via C-Type Lectin Domain Can Suppress HIV-1 Transfer - Dodagatta-Marri, Eswari; Mitchell, Daniel A.; Pandit, Hrishikesh; Sonawani, Archana; Murugaiah, Valarmathy; Idicula-Thomas, Susan; Nal, Béatrice; Al-Mozaini, Maha M.; Kaur, Anuvinder; Madan, Taruna; Kishore, Uday (Frontiers in Immunology, 2017)
Surfactant protein SP-D is a soluble C-type lectin, belonging to the collectin (collagen-containing calcium-dependent lectin) family, which acts as an innate immune pattern recognition molecule in the lungs and other mucosal surfaces. Immune regulation and surfactant homeostasis are salient functions of SP-D. SP-D can bind to a range of viral, bacterial and fungal pathogens and trigger clearance mechanisms. SP-D binds to gp120, the envelope protein expressed on HIV-1, through its C-type lectin or carbohydrate recognition domain (CRD). This is of importance since SP-D is secreted by human mucosal epithelial cells and is present in the female reproductive tract including vagina. Another C-type lectin, Dendritic Cell-Specific Intercellular adhesion molecule-3-Grabbing Non-integrin (DC-SIGN), present on the surface of the dendritic cells, also binds to HIV-1 gp120 and facilitates viral transfer to the lymphoid tissues. Dendritic cells are also present at the site of HIV-1 entry, embedded in vaginal or rectal mucosa. In the present study, we report a direct protein-protein interaction between recombinant forms of SP-D (rfhSP-D) and DC-SIGN via their C-type lectin domains. Both SP-D and DC-SIGN competed for binding to immobilized HIV-1 gp120. Pre-incubation of Human Embryonic Kidney (HEK) cells expressing surface DC-SIGN with rfhSP-D significantly inhibited the HIV-1 transfer to activated PBMCs. In silico analysis revealed that SP-D and gp120 may occupy same sites on DC-SIGN, which may explain the reduced transfer of HIV-1. In summary, we demonstrate, for the first time, that DC-SIGN is a novel binding partner of SP-D, and this interaction can modulate HIV-1 capture and transfer to CD4+ T cells. In addition, the present study also reveals a distinct mechanism of host defense by SP-D against HIV-1.